Furor, Fury, Voracity and Discomposure: The Evaluation of Women’S Passional Excess in Judicial Records of Late-Colonial Chile; [el Furor, la Furia, la Voracidad y la Descompostura: Evaluaciones del Exceso Pasional de Mujeres en Los Archivos Judiciales del Chile Tardo Colonial] - Labarca-Pinto, M (Universidad de Chile, Facultad de Filosofia y Humanidades, Departamento de Literatura, 2024)
This article explores how was identified and evaluated the emotional states of women who, seized by strong emotions, reacted in a violent and disorderly way executing “excesses” considered outside the bounds of law in Captaincy General of Chile during the 18th century. To do so, it examines judicial records involving violent behaviors, interpersonal disputes and family conflicts in which mood was scrutinized to explain what predisposed the person’s actions. It delves into how women’s passional excess or disturbed emotions were described, comparing it to the descriptions of men acting under similar predisposition to find out patterns behind this identification and the evaluation made by those involved in the altercation, judges, witnesses and lawyers. The article suggests that Chilean culture identified in “furor” and “fury”, translated into reactions that denoted “voracity” and “discomposure”, a seed of inner instability that was close to madness or that could be assimilated to it. This state of internal disturbance could affect both men and women, although the evaluation on its significance was in each case different. © 2024 Universidad de Chile, Facultad de Filosofia y Humanidades, Departamento de Literatura. All rights reserved.